Soil degradation risk prediction in an arid region (Northern Tataouine, Tunisia): using an empirical model coupling with remote sensing and GIS - Amal Gammoudi; Hanen Guesmi; Ahmed Tebini; Rafla Attia; Thouraya Sahli Chahed; Hosni Trabelsi (Environmental Research Communications)
The soil quality losses related to the water erosion is considered as a worldwide environmental hazard in arid regions, which is disturbing natural resources. In fact, it can affect land sustainability and agricultural production. In order to preserve the natural resources, different erosion models are applied. In this study, the combination of the model of RUSLE (Revised Universal Soil Loss equation) and the GIS (Geographic Information Systems) using the RS (remote sensing) techniques allows to detect vulnerable areas to soil degradation. The used model is related to five factors linked to the rainfall intensities, the topographic characteristics, the soil sensitivity, the agricultural practices and the vegetation cover. The application of this combination in the Ferch watershed (Southern Tunisia) indicates that the whole studied watershed has low soil erosion hazard (90.4%). Indeed, the high to severe soil erosion hazard are mainly characterized the mountainous zones. As a consequence, this work can be useful to ensure the appropriate environmental plan for sustainable soil conservation.